0500 STOPBANG QUESTIONNAIRE CORRECTLY DETECTS THE ABSENCE OF OBSTRUCTIVE SLEEP APNEA IN THE FIRST TRIMESTER OF PREGNANCY. (28th April 2017) - Sequeira, T; Bublitz, M; Adodoadji, E; Livingston, Z; Bourjeily, G
Abstract: Introduction: Sleep disordered breathing (SDB) is a common occurrence in pregnancy but data assessing the performance of screening tools are scarce in this population. The performance of screening questionnaires may also vary by the stage of pregnancy. The aim of this study was to examine progression of SDB and daytime sleepiness around conception and assess the ability of the STOPBANG and Epworth Sleepiness Scale (ESS) questionnaires to detect obstructive sleep apnea (OSA) in the first trimester of pregnancy. Methods: Women with obesity in the first trimester of a singleton pregnancy were recruited. Participants answered sleep questionnaires (STOPBANG and ESS) regarding current symptoms that occurred since conception (c-) and symptoms that were present prior to pregnancy (pre-). Participants also underwent a level III home sleep apnea test. Sleep apnea was defined as apnea hypopnea index (AHI) ≥5 events per hour and hypopnea defined based on 3% oxygen desaturation. Descriptive statistics, Pearson's correlation coefficient, non-paired t-test, and sensitivity and specificity analyses were performed. Results: A total of 105 women were recruited. Mean age was 29 ± 6; mean BMI was 34.3 ± 8. Thirty percent of women were nulliparous, 10% had pre-gestational hypertension and 2% had pre-gestational diabetes. Mean gestational age at enrollment was 10.5 ± 2 weeks. Eighteen percent of women had OSA. Pre- and c-STOPBANG, correlated strongly (r=0.86, p<0.05), and so did pre-ESS and c-ESS (r=0.80, p<0.05). However, average scores were significantly higher in the 1 st trimester (STOPBANG 2.32 ± 1.1 vs. 2.14 ± 1.1, p=0.009, ESS 11 ± 5.3 vs. 8 ± 5.1, p<0.0001) compared to pre-conception. C-STOPBANG and pre-ESS scores were significantly associated with OSA diagnosis (p=0.003 and p=0.03, respectively). Specificity of both pre and c-STOPBANG was 97.5% whereas sensitivity was <17%. Sensitivity of pre-ESS scores was 61% but specificity was poor for both pre- and c-ESS scores. Conclusion: The STOPBANG questionnaire demonstrated good ability to correctly detect patients without a diagnosis of OSA but limited ability to identify patients with OSA. Symptoms of sleep-disordered breathing and daytime sleepiness worsen as early as the first trimester of pregnancy compared to preconception. Support (If Any): NICHD 5R01HD078515-03